The Modern Regularity of Institutionalized Racism Towards Black Americans - Tadros, Eman; Tadros, George (Utan Kayu Publishing, 2023)
African Americans have faced persistent institutionalized barriers and systemic racism both historically and in the present day. One of the most glaring manifestations of this is the racial disproportionality observed in incarceration rates. This paper delves into specific domains, such as the justice and social welfare systems, where institutional discrimination is evident, contributing to the disenfranchisement of African Americans. It further addresses the gap in literature concerning the impacts of such racial disproportionality in incarceration, especially the systemic challenges faced post-incarceration. The objective of this research is to delineate the facets of institutionalized racism towards African Americans in the context of incarceration and to propose evidence-based clinical interventions for professionals working with this demographic.